Solid Waste Disposal and Management System in Netrokona Sadar Municipality Area of Netrokona District (Journal of Environmental Science and Natural Resources, 2025)
Efficient solid waste management in urban areas like Netrokona Sadar municipality remains a pressing concern. A study conducted from December 17 to 20, 2023, surveyed 60 households to assess current methods, environmental and health impacts, and links with respondent characteristics, aiming to offer sustainable guidelines. Results reveal an average solid waste generation of 0.28 kg per person per day, with organic materials (53.83%) and plastic (26.95%) dominating. Demographically, the community is diverse, with young adults (43.3%), varying educational levels (from illiteracy to beyond secondary, 23.33%), and predominant occupations in rickshaw pulling (30%) and labor (26.67%). Correlation analysis indicates positive relationships between waste generation and household characteristics such as monthly income, family size, education level, and occupation. Notably, age showed no significant correlation. House-to-house collection systems are preferred (48.33%), yet challenges persist due to inadequate resources. The study highlights strong correlations between waste generation and education (r = 0.2732, P < 0.05), occupation (r = 0.4788, P < 0.001), income (r = 0.6806, P < 0.01), and family size (r = 0.5764, P < 0.01). Higher education, specific occupations, increased income, and larger families correlate with higher waste generation rates. This research illuminates the complex interplay between socio-economic factors and waste generation behaviors. It emphasizes the need for customized waste management strategies, including enhanced infrastructure, public awareness initiatives, and resource allocation, to effectively address urban waste disposal challenges.Environ. Sci. & Natural Resources, 14(1&2): 10-15, 2025